Analisis Prediksi Kebangkrutan Dengan Menggunakan Metode Altman Z-Score, Zmijewski, Springate Dan Grover Pada PT. Smartfren Telecom Tbk: Analisis Prediksi Kebangkrutan Dengan Menggunakan Metode Altman Z-Score, Zmijewski, Springate Dan Grover Pada PT. Smartfren Telecom Tbk - Nur Novi Trianti Sakinah; PUJI, PUJI MUNIARTY (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
Bankruptcy is a condition of the company that shows the company's inability to operate properly due to severe financial difficulties. The purpose of this research is to know and measure the financial health condition of PT. Smartfren Telecom Tbk using Altman Z-Score, Zmijewski, Springate and Grover methods. The population is 13 years with the period 2007-2019 and the sample is 10 years with the period 2010-2019. This type of research is descriptive research using bankruptcy method and one sample t-test. The result of the study is altman Z-Score method, Springate and Grover predict PT. Smartfren Telecom Tbk does not have the potential to go into bankruptcy while Zmijewski's method predicts PT. Smartfren Telecom Tbk has the potential to go into bankruptcy. Based on the results of one sample t-test test calculation and the amount of standard deviation value obtained Zmijewski method is a relevant and accurate method to predict bankruptcy at PT. Smartfren Telecom Tbk.